For a new dialogue between theoretical and empirical studies in evo-devo - Fusco, Giuseppe (Frontiers in Ecology and Evolution, 2015)
Despite its potentially broad scope, current evo-devo research is largely dominated by empirical developmental studies, whereas comparably little role is played by theoretical research. I argue that this represents an obstacle to a wider appreciation of evo-devo and its integration within a more comprehensive evolutionary theory, and that this situation is causally linked to a limited exchange between theoretical and experimental studies in evo-devo. I discuss some features of current theoretical work in evo-devo, highlighting some possibly concurring impediments to an effective dialogue with experimental studies. Finally, I advance two suggestions for enhancing fruitful cross-fertilization between theoretical and empirical studies in evo-devo: (i) to broaden the scope of evo-devo beyond its current conceptualization, teaming up with other variational approaches to the study of evolution, and (ii) to develop more effective forms of scientific interaction and communication.